PENGGUNAAN PATH ANALYSIS UNTUK MEMEDIASI PENGARUH KEPEMILIKAN MANAJERIAL TERHADAP RISIKO DALAM MENEKAN KONFLIK KEAGENAN - KARTIKA N (Jurnal Bisnis dan Akuntansi, 2006)
This research develop the models of agency conflict with positioning of managerial ownership as intervening variable among dividend policy, debt policy and institutional ownership toward risk taking. Path analysis is used for running of 60 sample for manufacture companies that listed at Jakarta Stock Exchange in 1995-1996. Results indicate that managerial ownership has significant positive influence to risk taking, debt policy and institutional have significant negative influence to managerial ownership. So this mechanism can use as control device to mitigate the agency conflict. Inverse, result find that dividend policy is positive and significant to managerial ownership consequently, this mechanism can not mitigate the agency conflict. Finally results show that managerial ownership intervene the influence among debt policy and institutional ownership to risk talcing. Manager's decision must be focused to control the agency conflict for increasing value of the firm and stockholder's wealth fare.